Adaptation and Validation of the Scale for Chinese Preschool Teachers’ Self-Efficacy (SCPTSE): Based on Classical Test Theory and Item Response Theory - Hao Lu; Xiumin Li; Kejian Li (Behavioral Sciences, 2025)
Preschool teachers’ self-efficacy is essential to improve their professional development and the quality of early childhood education. This study adapted and validated the Scale for Chinese Preschool Teachers’ Self-Efficacy (SCPTSE) based on the Ohio State Teacher Efficacy Scale (OSTES), in accordance with Bandura’s Social Cognitive Theory. Following a rigorous four-stage cross-cultural adaptation procedure, the 21-item SCPTSE was administered to 882 in-service preschool teachers from Zhejiang, Henan, and Shaanxi provinces in China (M age = 30.41, SD = 6.05). Both CTT and IRT frameworks were employed to evaluate the scale’s psychometric properties. Under CTT, the SCPTSE demonstrated high internal consistency (α = 0.980), and CFA supported a robust three-factor structure—instructional strategies, classroom management, and child engagement—with excellent model fit (RMSEA = 0.079; SRMR = 0.025; CFI = 0.953; TLI = 0.947; NFI = 0.945; IFI = 0.953; PNFI = 0.837; PGFI = 0.700). Under IRT, all three sub-scales demonstrated strong unidimensionality (HIS = 0.812, HCM = 0.800, HCE = 0.818), the SCPTSE’ items demonstrate excellent discrimination capabilities(all a > 1.70), overall reasonable difficulty(b1 < b2 < b3 < b4), and balanced information distribution. Nevertheless, the relatively low-difficulty design (e.g., b1) indicates room for improvement. Notably, cultural adaptation efforts ensured the scale’s contextual relevance to China’s preschool education system. The SCPTSE thus offers a valid, reliable, and culturally responsive tool for assessing self-efficacy of Chinese in-service preschool teachers and holds promise for informing targeted professional development and comparative international research.